Lignin-Degrading Enzymes and the Potential of Pseudomonas putida as a Cell Factory for Lignin Degradation and Valorization - Qing Zhou; Annabel Fransen; Han de Winde (Microorganisms)
Efficient utilization of lignin, a complex polymer in plant cell walls, is one of the key strategies for developing a green and sustainable bioeconomy. However, bioconversion of lignin poses a significant challenge due to its recalcitrant nature. Microorganisms, particularly fungi and bacteria, play a crucial role in lignin biodegradation, using various enzymatic pathways. Among bacteria, Pseudomonas putida is considered a promising host for lignin degradation and valorization, due to its robust and flexible metabolism and its tolerance to many noxious and toxic compounds. This review explores the various mechanisms of lignin breakdown by microorganisms, with a focus on P. putida’s metabolic versatility and genetic engineering potential. By leveraging advanced genetic tools and metabolic pathway optimization, P. putida can be engineered to efficiently convert lignin into valuable bioproducts, offering sustainable solutions for lignin valorization in industrial applications.